Clinical manifestations of neuroblastoma with head and neck involvement in children. (June 2017) - Alvi, Sameer; Karadaghy, Omar; Manalang, Michelle; Weatherly, Robert
Abstract: Objective: The purpose of our study is to review our 15-year experience with pediatric patients who have been diagnosed with neuroblastoma, and to determine their most frequent head and neck manifestations and symptoms. Study design: Retrospective chart review of electronic medical record. Setting: An academic, tertiary care pediatric hospital. Subjects and Methods: IRB approval from the Office of Research Integrity at Children's Mercy Hospital was obtained. The hospital tumor database was analyzed to identify patients with neuroblastoma, ganglioneuroblastoma, and esthesioneuroblastoma diagnosed between 1997 and 2012. We recorded the various clinical signs and symptoms these patients displayed at their initial presentation, focusing on patients with head and neck involvement. We then determined the relative incidence of these various findings. Results: Our review yielded 118 patients diagnosed with neuroblastoma, ganglioneuroblastoma, or esthesioneuroblastoma over our 15 year study period. 7 of the 118 patients were diagnosed with primary tumors of the head and neck. Another 19 patients had metastatic head and neck involvement. For those with primary disease, presence of a neck mass and signs of Horner's syndrome were the most common findings. For metastatic disease, craniofacial bony metastasis was the most frequent finding in our study. Conclusions: Based on our data, there are a handful of findings that occur frequently in pediatric head and neck neuroblastoma. Any persistent neck mass, unexplained Horner's syndrome, or periorbital ecchymosis should be carefully evaluated. This study should serve as an aid for the otolaryngologist to be aware of the possible manifestations of this malignancy in children.